Relevance of nanocomposite packaging on the stability of vacuum-packed dry cured ham. (August 2016) - Lloret, Elsa; Fernandez, Avelina; Trbojevich, Raul; Arnau, Jacint; Picouet, Pierre A.
Abstract: In this study effects of a novel high barrier multilayer polyamide film containing dispersed nanoclays (PAN ) on the stability of vacuum packed dry-cured ham were investigated during 90 days refrigerated storage in comparison with non-modified multilayer polyamide (PA) and a commercial high barrier film. Characteristic bands of the mineral in FT-IR spectra confirmed the presence of nanoclays in PAN, enhancing oxygen transmission barrier properties and UV protection. Packaging in PAN films did not originate significant changes on colour or lipid oxidation during prolonged storage of vacuum-packed dry-cured ham. Larger oxygen transmission rates in PA films caused changes in CIE b * during refrigerated storage. Ham quality was not affected by light exposition during 90 days and only curing had a significant benefit on colour and TBARS, being cured samples more stable during storage in all the packages used. Packaging of dry-cured ham in PAN was equivalent to commercial high barrier films. Highlights: Polyamide nanocomposites may have advantages over current high barrier commercial films. Barrier properties of a multilayer polyamide film were enhanced by nanoclays. The PA6-nanocomposite was tested during storage of vacuum-packed dry-cured ham. The PA-6 nanocomposite had no negative effects on dry-cured ham quality. Curing with nitrite had a significant benefit on colour and TBARS stability